Treacherous women of imperial Japan : patriarchal fictions, patricidal fantasies - Raddeker, Helene Bowen, 1952- (Nissan Institute/Routledge Japanese studies series., 1997)
An inspiring analysis of events surrounding two women's attempted assassination of the Emperor of Japan, and the separate penalties faced by these women both in terms of their death sentences and the wider context surrounding their lives.